Optimizing Data Visualization for Research and Community Service Management : Evaluating SIMLPPM Universitas Jambi Using the HOT-FIT Model - Jodion Siburian; Pradita Eko Prasetyo Utomo; Dawam Suprayogi (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2024)
The increasing demand for efficient data management in higher education has highlighted the need for advanced information systems that support research and community service activities. At Universitas Jambi, the Sistem Informasi Penelitian dan Pengabdian kepada Masyarakat (SIMLPPM) is the primary platform for managing research data. However, its usability remains limited due to restricted accessibility, unstructured data categorization, and inadequate visualization tools. This study aims to enhance SIMLPPM by developing an interactive dashboard to improve data presentation, user trust, and decision-making efficiency. The research employs the Human-Organization-Technology FIT (HOT-FIT) model to evaluate user satisfaction and system effectiveness by surveying 128 faculty members. The findings indicate that leadership support, organizational structure, and facilities significantly influence user satisfaction and system adoption, while information and service quality have minimal impact. The study underscores the importance of system usability and administrative support over purely technical attributes. Future research should explore AI-driven analytics and expand the evaluation across multiple institutions to enhance data accessibility and user engagement in research management.